S-28-7: GENE VARIANTS THAT NEUTRALIZE MORTALITY RISK FROM HYPERTENSION AND THEREBY INCREASE LIFESPAN. (January 2023) - Morris, Brian J.; Chen, Randi; Donlon, Timothy A.; Maskai, Kamal H.; Willcox, D. Craig; Davy, Philip M.C.; Allsopp, Richard C.; Willcox, Bradley J.
Abstract : Objective: To determine whether longevity genes extend lifespan by protecting against hypertension and/or other cardiometabolic diseases. Design: Prospective population based longitudinal study. Methods: We followed a cohort of 3, 584 Japanese American men living on Oahu, Hawaii, who were recruited from 1965 to 1968 for the Kuakini Honolulu Heart Program, until Dec 2019 when 99% were deceased. Genotype frequencies of longevity associated SNPs in the genes FOXO3, PIK3R1, GHR, MAP3K5, CTGF, EGFR, FLT1, SIRT5 and SIRT7 were compared between subjects with and without ageing related diseases. Results: For FOXO3, PIK3R1, GHR, FLT1, MAP3K5 and EGFR, but not the other 3 longevity genes, longevity genotype increased lifespan by protecting against elevated risk of death posed by having hypertension, coronary artery disease or diabetes (cardiometabolic diseases, CMD), as follows: For FOXO3, covariate adjusted hazard ratios (HRs) for each of 9 longevity associated SNPs were 0.82 to 0.95 ( P = 0.00008 to 0.020); covariate adjusted haplotype analysis HR = 0.81 ( P = 0.0003); survival curve difference (covariate adjusted Cox proportional HR) was P = 0.0002. Strikingly, those men with a CMD who had the FOXO3 longevity genotype had similar survival as men without CMD. For the other genes, hazard ratios for reduction in the elevated risk of mortality from various CMDs conferred by the longevity associated SNP were: for PIK3R1, from hypertension or coronary artery disease, 1.17, for GHR, from hypertension, 1.20, for FLT1, from hypertension, 1.78, for MAP3K5, from CMD, 1.23, EGFR, from CMD, 1.10. None protected against risk of death from cancer. Conclusions: 6 of 9 longevity genes exert their longevity effect by protecting against hypertension and/or other CMDs, possibly by amelioration of disease related cellular stress.